Atom-economical synthesis of a high silica CHA zeolite using a solvent-free route. Issue 95 (6th October 2015) - Wang, Xiong; Wu, Qinming; Chen, Chunyu; Pan, Shuxiang; Zhang, Weiping; Meng, Xiangju; Maurer, Stefan; Feyen, Mathias; Müller, Ulrich; Xiao, Feng-Shou
Abstract : A high silica CHA zeolite is successfully synthesized in the presence of a low-cost template of N, N, N -dimethylethylcyclohexylammonium bromide under solvent-free conditions. Abstract : A high silica CHA zeolite is successfully synthesized in the presence of a small amount of N, N, N -dimethylethylcyclohexylammonium bromide under solvent-free conditions. Catalytic tests for the selective catalytic reduction of NO x with NH3 (NH3 -SCR) and methanol-to-olefins (MTO) show that the sample from the solvent-free route exhibits comparable catalytic properties to that from the conventional route.